Autologous Matrix-Induced Chondrogenesis for Treatment of Focal Cartilage Defects in the Knee: A Follow-up Study. Issue 2 (26th February 2021) - Gille, Justus; Reiss, Ellen; Freitag, Moritz; Schagemann, Jan; Steinwachs, Matthias; Piontek, Tomasz; Reiss, Eric
Background: Autologous matrix-induced chondrogenesis (AMIC) is a well-established treatment for full-thickness cartilage defects. Purpose: To evaluate the long-term clinical outcomes of AMIC for the treatment of chondral lesions of the knee. Study Design: Case series; Level of evidence, 4. Methods: A multisite prospective registry recorded demographic data and outcomes for patients who underwent repair of chondral defects. In total, 131 patients were included in the study. Lysholm, Knee injury and Osteoarthritis Outcome Score (KOOS), and visual analog scale (VAS) score for pain were used for outcome analysis. Across all patients, the mean ± SD age of patients was 36.6 ± 11.7 years. The mean body weight was 80.0 ± 16.8 kg, mean height was 176.3 ± 7.9 cm, and mean defect size was 3.3 ± 1.8 cm 2 . Defects were classified as Outerbridge grade III or IV. A repeated-measures analysis of variance was used to compare outcomes across all time points. Results: The median follow-up time for the patients in this cohort was 4.56 ± 2.92 years. Significant improvement ( P < .001) in all scores was observed at 1 to 2 years after AMIC, and improved values were noted up to 7 years postoperatively. Among all patients, the mean preoperative Lysholm score was 46.9 ± 19.6. At the 1-year follow-up, a significantly higher mean Lysholm score was noted, with maintenance of the favorable outcomes at 7-year follow-up. The KOOS also showed a significant improvement of postoperative values compared with preoperative data. The mean VAS had significantly decreased during the 7-year follow-up. Age, sex, and defect size did not have a significant effect on the outcomes. Conclusion: AMIC is an effective method of treating chondral defects of the knee and leads to reliably favorable results up to 7 years postoperatively.